An investigation into the relationship between light absorption budget and trophic status in inland waters - Rodrigues, Thanan; Alcantara, Enner [UNESP]; Rotta, Luiz [UNESP]; Bernardo, Nariane [UNESP]; Watanabe, Fernanda [UNESP] (Elsevier B.V., 2020)
The optical properties of the water can give comprehensive information about the in-water constituents which is directly related to concentration, size and composition, all essential for the development of bio-optical algorithms. Aiming to provide new observations about optical properties of water in two distinct reservoirs situated along the cascade system of Tiete River: Barra Bonita (BB) and Nova Avanhandava (Nav), this study described and discussed their inherent optical properties (IOPs) in terms of the absorption contribution. BB showed a dominance in the phytoplankton fraction at all visible wavelengths, and Nav by nonalgal particle absorption (a(NAP)), mainly at the blue and green wavelengths. The mass-specific absorption coefficient of phytoplankton at 443 nm observed in Nav and BB corroborated with the assumption that the trophic state decreases from oligotrophic to hypereutrophic. The a(NAP) (lambda) did not show a seasonal pattern between field campaigns and reservoirs. The absorption coefficient of particulate enhanced the strong influence of phytoplankton pigments along the visible spectrum in BB, whereas Nav only displayed the peak at 675 nm represented by chlorophyll a absorption and high contribution of non-algal particle and colored dissolved organic matter in the blue region. These findings recommend the use of different modelling approaches to estimate water quality parameters from both sites when the inputs of the models consider the specific information about the IOPs and their relation with the in-water constituents.
Keywords: Bio-optical properties; Cascade system; Tropical reservoirs